Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer: the 1st one is the correct answer.
Step-by-step explanation:
Answer:
I will choose the first option
Step-by-step explanation:
[tex]gradient(m) = \frac{y2 - y1}{x2 - x1} \\ \\ taking \: x1 = - 3 \\ x2 = 4 \\ y1 = 4 \\ y2 = - 1 \\ \\ m = \frac{ - 1 - 4}{4 - - 3} \\ m = \frac{ - 5}{7} \\ \\ y - y1 = m(x - x1) \\ y - 4 = \frac{ - 5}{7} (x - -3) \\ \\ y - 4 = \frac{ - 5}{7} (x + 3)[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.